Blood Lead Exposure and Association With Hepatitis B Core Antibody in the United States: NHANES 2011–2018 - Kexing Han; Tengyao He; Siran Huang; Weijie Sun; Yufeng Gao (Frontiers in Public Health, 2022)
The objective of this project was to explore the distribution and related factors of blood lead and the association between blood lead and hepatitis B core antibody (HBcAb). All the data were from the U.S. National Health and Nutrition Examination Survey (NHANES). In total, 15,097 (aged 20–80 years) participants were included. Participants without a history of blood transfusion were more likely to be exposed to lower levels of blood lead [−2.30 (−3.13, −1.47) for HBcAb (–) and −2.23 (−4.54, 0.08) for HBcAb (+)]. The odds ratio (OR) of HBcAb (+) increased with blood lead and the result was 1.09 (1.06, 1.12). This study showed that older adults, men, people with a lower education level, a lower ratio of family income to poverty (PIR), a lower body mass index (BMI), or a history of blood transfusion, people who lived with a companion or with a total number of people in the family >3, people living in the United States for a longer time, U.S. citizens by birth or naturalization, and people not born in the United States were associated with higher blood lead exposure, and blood lead had a positive association with HBcAb (+).